Pollution under environmental regulation in energy markets - Gullì, Francesco (Lecture notes in energy, 2025)
Pollution under environmental regulation in energy markets provides a study of environmental regulation when energy markets are imperfectly competitive. This theoretical treatment focuses on three relevant cases of energy markets. First, the residential space heating sector where hybrid regulation such as taxation and emissions trading together are possible. Second, the electricity market where transactions are organized in the form of multi-period auctions. Third, namely natural gas (input) and electricity (output) markets where there is combined imperfect competition in vertical related energy markets.   The development of free or low carbon technologies supported by energy policies, aiming at increasing security of supply, is also explored whilst considering competition policies that reduce market power in energy markets thus improving market efficiency. Pollution Under Environmental Regulation in Energy Markets discusses the key issues of whether imperfect competition can lessen the ability of environmental policy to reduce pollution and/or to minimize the cost of meeting environmental targets.   Policymakers, analysts and researchers gain a thorough understanding of the performance of environmental policy from Pollution Under Environmental Regulation in Energy Markets leading to better design of simulation models of performance and costs of environmental regulation. 1.Introduction and summary -- 2. Pollution under hybrid environmental regulation: the case of space heating -- 3. Pollution under Environmental regulation within multi-period auctions: the case of electricity markets -- 4. Pollution under imperfect competition in vertical related energy markets.